2006
DOI: 10.1093/ecam/nel049
|View full text |Cite
|
Sign up to set email alerts
|

Housing in Pyramid Counteracts Neuroendocrine and Oxidative Stress Caused by Chronic Restraint in Rats

Abstract: The space within the great pyramid and its smaller replicas is believed to have an antistress effect. Research has shown that the energy field within the pyramid can protect the hippocampal neurons of mice from stress-induced atrophy and also reduce neuroendocrine stress, oxidative stress and increase antioxidant defence in rats. In this study, we have, for the first time, attempted to study the antistress effects of pyramid exposure on the status of cortisol level, oxidative damage and antioxidant status in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 34 publications
2
19
0
Order By: Relevance
“…There was no significant difference in the results for these parameters between the PE-2 and PE-4 rats except for erythrocyte GSH-Px activity which was significantly more in the PE-2 rats than in the PE-4 rats. The possible explanations for the beneficial effects of pyramid on the above parameters are discussed in detail in our earlier studies (1,2,13,14,15). Although many beneficial changes have been reported and repeatedly observed in the pyramids (16), some mystics have complained that when they spend a great deal of time in the pyramid for meditational purposes, they felt they received 'too much energy'.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…There was no significant difference in the results for these parameters between the PE-2 and PE-4 rats except for erythrocyte GSH-Px activity which was significantly more in the PE-2 rats than in the PE-4 rats. The possible explanations for the beneficial effects of pyramid on the above parameters are discussed in detail in our earlier studies (1,2,13,14,15). Although many beneficial changes have been reported and repeatedly observed in the pyramids (16), some mystics have complained that when they spend a great deal of time in the pyramid for meditational purposes, they felt they received 'too much energy'.…”
Section: Resultsmentioning
confidence: 88%
“…Our scientific studies with mini wooden replica models of the Great pyramid of Giza have shown that exposure of adult female Wistar rats to pyramid environment reduces stress, oxidative stress and increases antioxidant defence in them (1,2). Beneficial effects of pyramid exposure on other parameters namely improved wound healing in rats (3,4,5) have also been reported.…”
Section: Introductionmentioning
confidence: 94%
“…Housing of rats within a small pyramid aligned to the north-south axis reduced the oxydative damage and neuroendocrine stress of rats chronically restrained 14 d (6 h daily) within a wire mesh[127,128]. Beneficial effect of the pyramid was dependent on its north-south alignment[129].…”
Section: Can the Aging Be Delayed?mentioning
confidence: 99%
“…Both groups maintained in their home cages for 7 and 14 days. The third group (Pyramid housed group) in which Nx rats housed within the wooden pyramid (6 hr/day) for 7 and 14 days [24].…”
Section: Experimental Designmentioning
confidence: 99%